Double-phase stainless steel plate with excellent low-temperature fracture toughness for polar region ship and manufacturing method of double-phase stainless steel plate
By optimizing the composition design and process flow of duplex stainless steel plates, the problems of steel plate strength, low temperature toughness and fracture toughness in polar environments are solved, and high strength, low temperature resistance and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510097148.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-09
AI Technical Summary
The prior art is difficult to provide marine duplex stainless steel plates with good strength, low temperature toughness and fracture toughness in polar environments, especially in ice-zone environments, where steel plates need to have higher corrosion resistance and toughness.
By optimizing the component design, the synergistic effect of elements such as C, Si, Mn, Cr, Ni, Mo, N, Cu, La, Ce is controlled to control the austenite phase ratio between 60% and 80% and the ferrite phase ratio between 20% and 40%. The EAF arc furnace-AOD converter-VOD vacuum refining process is used for smelting, and the two-stage rolling and solid solution treatment is used to ensure the low-temperature fracture toughness of the steel plate.
It realizes the high strength, low temperature resistance and good fracture toughness of duplex stainless steel plates, meets the service requirements under harsh conditions of polar marine environments, and maintains good corrosion resistance.
Smart Images

Figure CN119956208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials, and in particular relates to a polar ship duplex stainless steel plate with excellent low-temperature fracture toughness and a manufacturing method thereof. Background Art
[0002] With the opening of the Arctic route, polar oil tankers, polar LPG ships, polar container ships, polar chemical tankers and other ship types have also begun to develop rapidly. Because the above-mentioned ships need to serve in ice areas for a long time, the hull structure will inevitably collide with the ice during navigation. Therefore, the steel plates used to build polar ships are required to have good strength, low-temperature toughness and fracture toughness. Duplex stainless steel has both the good strength and corrosion resistance of ferritic stainless steel and the good toughness and welding performance of austenitic stainless steel. With its excellent mechanical properties and corrosion resistance, it is widely used in the construction of chemical tankers, oil tankers and other ships used to transport highly corrosive substances. Therefore, in order to meet the growing demand for polar ship construction, it is urgent to develop marine duplex stainless steel plates that can be used in polar environments.
[0003] The invention patent with publication number CN117535478A proposes a method for preparing high-performance duplex stainless steel, wherein the chemical composition and mass percentage of the stainless steel ingot are: C: 0.01-0.02%, Si: 0.03-0.04%, Mn: 8.25-8.40%, Cr: 21.02-22.03%, Ni: 0.54-0.56%, Mo: 0.91-1.02%, Cu: 0.30-0.32%, N: 0.24-0.25%, P≤0.01%, S≤0.01%, and the balance is Fe and unavoidable impurities. The patent adopts a higher content of Mn, which can ensure higher strength, but will cause a serious decrease in the corrosion resistance of the steel, and will also affect the toughness of the steel. Its component system and production process are essentially different from the present invention.
[0004] The invention patent with publication number CN101215674 proposes an economical duplex stainless steel alloy material and its preparation method. The composition and mass percentage of the alloy material are: 0<C≤0.04%, 0<S≤0.01%, 0<Si≤1.0%, 0<P≤0.015%, Cr: 18.0~20.0%, Mn: 5.0~7.0%, N: 0.15~0.25%, B: 0.001~0.01%, rare earth Ce or Y: 0.005~0.20%, and the rest is iron. The chemical composition of the patent does not contain Ni and Mo. On the one hand, its pitting corrosion equivalent PREN is only 22.5~27.5, which is much lower than the present invention. On the other hand, the component system cannot make the material have good low temperature toughness. Its component design ideas and material mechanical properties are essentially different from the present invention.
[0005] The invention patent with publication number CN116904854A proposes a corrosion-resistant high-strength duplex stainless steel and its preparation method, which includes, by weight percentage: C0.09%~0.14%, Si≤0.80%, Mn≤0.80%, P≤0.035%, S≤0.030%, Cr20.00%~22.00%, Ni 4.80%~5.80%, 0<Mo≤0.20%, Ti0.35%~0.65%, 0<Al≤0.13%, 0<N≤0.035%, and the balance is iron and inevitable impurities. The chemical composition of the patent is quite different from that of the present invention, and its preparation method is upsetting and drawing forging, while the present invention adopts rolling for production and manufacturing, and the patent has no embodiment in the mechanical properties such as strength and toughness of the material. Therefore, compared with the present invention, there are essential differences in chemical composition, production process and mechanical properties. Summary of the invention
[0006] The purpose of the present invention is to overcome the above problems and shortcomings and provide a polar marine duplex stainless steel plate with excellent low-temperature fracture toughness and a manufacturing method thereof under the premise of ensuring good strength and corrosion resistance of duplex stainless steel. The maximum thickness of the duplex stainless steel plate is 60 mm, and the low-temperature toughness can reach -100°C.
[0007] The object of the invention is achieved in this way:
[0008] A polar ship duplex stainless steel plate with excellent low-temperature fracture toughness, the composition of the steel plate is as follows by weight percentage: C: 0.001%-0.01%, Si: 0.2%-0.5%, Mn: 0.5%-1.5%, P≤0.02%, S≤0.002%, Cr: 21%-22%, Ni: 7%-9%, Mo: 2%-3%, N: 0.1%-0.3%, Cu: 2%-3%, La: 0.0055%-0.0095%, Ce: 0.0045%-0.0085%. The balance is iron and unavoidable impurities.
[0009] Furthermore, the microstructure of the duplex stainless steel plate is austenite and ferrite, wherein the volume percentage is: austenite phase: 60% to 80%, ferrite: 20% to 40%; the average grain size of the duplex stainless steel plate can be controlled at 10 to 20 μm.
[0010] Furthermore; the yield strength of the stainless steel plate is ≥605MPa, the tensile strength is ≥812MPa; the impact energy at -80℃ is ≥180J, the impact energy at -100℃ is ≥142J, the non-plastic transition temperature NDTT is ≤-70℃, the low-temperature elongation at -40℃ is ≥35%, the Z-direction performance is ≥63%, and the low-temperature fracture CTOD of the base material and the heat-affected zone at -20℃, -40℃ and -60℃ is greater than 0.2mm.
[0011] The reasons for the composition design of the present invention are as follows:
[0012] C: It is the most basic element in steel and also a common strengthening element. With the increase of carbon content, the strength and hardness of steel will be significantly improved. However, due to its precipitation strengthening effect, carbides will be formed and precipitated at the grain boundaries, resulting in a decrease in corrosion resistance. At the same time, it will also reduce the impact toughness and welding performance of the material. Therefore, its content should be strictly controlled. Considering its impact on the performance of steel, the C content should be controlled within 0.01%.
[0013] Si: It is also a common element in steel. It can promote the formation of ferrite, thereby improving the strength of steel. It can also be used as a deoxidizer in the smelting process. Its content should be controlled above 0.2%. However, a high silicon content will reduce the impact toughness of steel. Therefore, considering its impact on strength and toughness, the Si content should be controlled at 0.2% to 0.5%.
[0014] Mn: It is a common austenitizing element, which can improve the strength of steel. Its austenitizing effect can replace the precious metal nickel to a certain extent. However, too high manganese content will lead to a decrease in the corrosion resistance of the steel, and the formed metal interstitial phase will also lead to a decrease in impact toughness. Therefore, its upper limit must also be strictly controlled. The Mn content in the steel of the present invention should be controlled at 0.5% to 1.5%.
[0015] Cr: It is the main element in stainless steel, the most important corrosion-resistant element, and the main ferrite-forming element. It can significantly improve the strength and hardness of steel. However, if the chromium content is too high, it will easily form a metal interstitial phase, and the surface quality of the steel plate will be affected due to the uneven oxide film formed. In order to ensure the performance of the steel and take into account the economy and surface quality, the Cr content in the present invention should be controlled at 21% to 22%.
[0016] Ni: It is a common element in stainless steel, which can promote the formation and stability of austenite, and can promote the transformation of steel from body-centered cubic to face-centered cubic, so as to obtain better strength and toughness. At the same time, it can also improve the poor thermoplasticity caused by copper in steel. As an important element for increasing the proportion of austenite phase in the present invention, in order to ensure the low-temperature toughness of steel, the Ni content should be controlled at 7% to 9%.
[0017] Mo: It is a common element in stainless steel. Similar to chromium, it is also a ferrite-forming element. It can improve the strength and corrosion resistance of steel, especially the ability to resist chloride corrosion. However, it will also promote the formation of metal interstitial phases, thereby reducing the toughness of steel. Therefore, the Mo content in the steel of the present invention should be controlled at 2% to 3%.
[0018] N: It is a common element in stainless steel and a common austenite-forming element. It can improve the strength and corrosion resistance of steel. However, when the nitrogen content is too high, the thermoplasticity of the steel decreases, which is not conducive to rolling deformation. Considering that the austenitizing effect of nitrogen can replace part of the precious metal nickel, the N content in the steel of the present invention is controlled at 0.1% to 0.3%.
[0019] Cu: It is a common corrosion-resistant element in steel, especially in the field of ships and marine engineering. It has a significant effect on the corrosion resistance in the marine environment. It can also improve the strength and hot workability of steel and improve the surface quality of steel plates. However, the addition of copper will cause the thermoplasticity of steel to drop significantly, and it needs to be used in combination with nickel. Therefore, the Cu content in the steel of the present invention is 2% to 3%.
[0020] La and Ce: have good deoxidation and desulfurization effects, improve the fluidity of steel, reduce non-metallic inclusions, make the steel structure dense and pure, improve the anisotropic properties of steel, and have a beneficial effect on improving the impact toughness of steel, especially the low-temperature impact toughness. The present invention adopts a method of composite addition of La and Ce, and controls the range of La to be 0.0055% to 0.0095% and the range of Ce to be 0.0045% to 0.0085%.
[0021] P and S are harmful elements in stainless steel and are not beneficial to either mechanical properties or corrosion resistance. Therefore, in the present invention, the P content is controlled to be below 0.02% and the S content is controlled to be below 0.002%.
[0022] The second technical solution of the present invention is to provide a method for manufacturing polar marine duplex stainless steel plate with excellent low-temperature fracture toughness, including smelting, rolling, and solid solution;
[0023] Smelting: including EAF electric arc furnace - AOD converter - VOD vacuum refining;
[0024] EAF electric arc furnace smelting:
[0025] The present invention adopts the process of EAF electric arc furnace - AOD converter - VOD vacuum refining furnace for smelting; alloy iron and scrap steel are melted in the EAF electric arc furnace, and then the molten steel in the electric arc furnace is injected into the AOD converter by using a ladle;
[0026] AOD converter smelting: oxygen and argon are injected into the molten pool. When the carbon content is higher than 0.05%, Ar 2 :O 2 =1:(1~1.5) low argon oxygen ratio for blowing, oxygen supply intensity is 3~5m 3 / (t·min), decarburization rate is 0.2~0.4% / min;
[0027] When the carbon content is reduced to 0.05%, the argon-oxygen ratio is increased to (3.5-4:)1; by adding reducing agents such as ferrosilicon, lime, and fluorite to deoxidize the molten steel and reduce the chromium in the slag, the Si content in the steel is controlled below 0.5%, and the basicity of the slag is controlled below 2.0; at the same time, argon blowing and stirring are strengthened, and aluminum powder is added to the slag;
[0028] VOD vacuum refining: VOD vacuum refining furnace is used to carry out deep decarburization of molten steel. First, oxygen blowing decarburization is carried out. During this period, the vacuum degree is controlled at 50-100mbar. The use of a higher vacuum degree can quickly extract a large amount of CO generated initially and accelerate the removal of carbon. When the carbon content in the molten steel reaches 0.03%, the vacuum degree is reduced to 20-40mbar. While ensuring the continuous decarburization reaction, excessive boiling and splashing of the molten steel due to excessive vacuum are avoided. When the carbon content reaches 0.01%, oxygen blowing is stopped. At this time, the vacuum degree is reduced to 1-10mbar, and the bottom stirring is strengthened to carry out vacuum decarburization. After decarburization, the chromium content in the steel generally decreases by 0.5%-0.8%. Ferrosilicon, lime, fluorite and other reducing agents are added again to reduce the molten steel to achieve chromium reduction and deoxidation and desulfurization of the molten steel. Most of the chromium, manganese and iron can also be reduced from the slag to the molten steel.
[0029] Rolling:
[0030] The ingot is loaded into the heating furnace at a furnace temperature of 800-850°C and kept warm for 1.5-2 hours. The uniform heating temperature is 1200-1250°C and kept warm for 2-2.5 hours. The ingot is rolled using a two-stage rolling technology. The first-stage rolling of the present invention is carried out in a low-temperature, high-pressure manner. The start rolling temperature is controlled at 1100-1150°C, the pass reduction rate is 20%-25%, and the first-stage final rolling temperature is 1050-1100°C. On the one hand, a lower start rolling temperature can accumulate a large amount of deformation storage energy inside the steel plate, providing sufficient driving force for subsequent recrystallization; on the other hand, a larger pass reduction rate can crush the ingot grains, obtain a uniform and fine structure in the dynamic recrystallization process, and ensure the toughness of the steel plate by refining the grains. The second stage is carried out in a small reduction manner, and the start rolling temperature is controlled at 1000-1050°C. This temperature is higher than the second stage start rolling temperature of the traditional duplex stainless steel rolling process, but is still above the recrystallization temperature of the duplex stainless steel, which can effectively inhibit the transformation of austenite to ferrite to ensure the toughness of the steel plate. At the same time, a pass reduction rate of 10% to 15% is used to release the deformation storage energy accumulated in the first stage of rolling, so that the steel plate is fully deformed, internal stress is eliminated, and edge cracks are avoided. The final rolling temperature is still controlled above 950°C to ensure that the entire deformation process is carried out in the recrystallization zone; the steel plate is air-cooled to room temperature after rolling.
[0031] Solid solution:
[0032] The present invention adopts a lower holding temperature and a longer holding time for solution treatment. When a lower solution temperature is adopted, the transformation of austenite to ferrite in the steel can be suppressed, thereby obtaining more austenite phases to ensure good low-temperature toughness of the steel plate. However, too low a solution temperature will cause the precipitation phase to be unable to be completely dissolved, affecting the mechanical properties and corrosion resistance of the steel plate. Therefore, the solution treatment process in the present invention is as follows: the holding temperature is 1030-1050°C, the net holding time is 5-10min / mm, and then the steel plate is taken out of the solution furnace and immediately placed in water for rapid cooling to obtain a fine and uniform microstructure to ensure the performance of the steel plate. The cooling rate is not less than 20°C / s, and the surface temperature of the steel plate after cooling is not higher than 50°C, and the average grain size can be controlled at 10-20μm. The austenite phase ratio is controlled at 60%-80%, and the ferrite phase ratio is controlled at 20%-40%.
[0033] Pickling:
[0034] The surface of the solution treated steel plate is cleaned with a HF+HNO3 mixed acid at a temperature not higher than 80°C to obtain a finished steel plate with a higher surface quality.
[0035] The beneficial effects of the present invention are:
[0036] (1) The ultra-low carbon composition design is adopted. By adding the synergistic effect of Si, Mn, Cr, Ni, Mo, N, Cu, La, Ce and other elements, the austenite phase region is expanded while ensuring its good strength and corrosion resistance. At the same time, the generation of precipitation phase is controlled, thereby achieving the effect of improving the low-temperature fracture toughness of the steel plate.
[0037] (2) The process of EAF electric arc furnace - AOD converter - VOD vacuum refining furnace is adopted to achieve deep decarburization of molten steel, and at the same time, it can obtain good deoxidation and desulfurization effects, control the content of harmful elements and non-metallic inclusions in steel, improve the purity of steel, and ensure the low-temperature fracture toughness of steel plates.
[0038] (3) A two-stage rolling technology is adopted, in which the first stage adopts a low temperature and large reduction method, which on the one hand provides a driving force for subsequent recrystallization, and on the other hand ensures the low-temperature toughness of the steel plate by refining the grains; the second stage adopts a high temperature and small reduction method to fully release the deformation energy and eliminate the internal stress, so as to ensure the plate shape and surface quality of the steel plate.
[0039] (4) Use a lower solution temperature and a longer holding time to inhibit the transformation of austenite to ferrite. At the same time, cool quickly after solution to obtain a fine and uniform structure to ensure the performance of the steel plate.
[0040] (5) The present invention prepares a polar marine duplex stainless steel plate, which has high strength (yield strength ≥ 605MPa, tensile strength ≥ 812MPa), low temperature resistance (-80℃ impact energy ≥ 180J, -100℃ impact energy ≥ 142J, no plastic transition temperature NDTT ≤ -70℃), (-40℃) low temperature elongation ≥ 35%, Z-direction performance ≥ 63%, low temperature fracture (-20℃, -40℃, -60℃) CTOD characteristic value of the parent material and the heat affected zone> 0.2mm, and the pitting corrosion performance is measured according to the ASTM G48 method A ferric chloride test method. The pitting corrosion rate of the steel plate is 0.0030-0.0065g / m 2 h; The intergranular corrosion performance was measured according to ASTM A262 method E and the steel plates showed no cracks; its good conventional mechanical properties, corrosion resistance, low-temperature fracture toughness, etc. can meet the technical requirements of marine steel plates for harsh and demanding service conditions in the polar marine environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a metallographic microstructure diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0042] The present invention will be further described below by way of examples.
[0043] The embodiment of the present invention performs smelting, rolling and solid solution according to the component ratio of the technical solution.
[0044] Rolling: Load the ingot into the heating furnace at a furnace temperature of 800-850℃ and keep it warm for 1.5-2 hours. The aquifer temperature is 1200-1250℃ and kept warm for 2-2.5 hours; two-stage rolling is adopted. The first stage rolling is carried out by low temperature and large reduction. The start rolling temperature is controlled at 1100-1150℃, the pass reduction rate is 20%-25%, and the first stage final rolling temperature is 1050-1100℃; the second stage is carried out by high temperature and small reduction. The start rolling temperature is controlled at 1000-1050℃, the pass reduction rate is 10%-15%, and the final rolling temperature is still controlled above 950℃. The steel plate is air-cooled to room temperature after rolling.
[0045] Solid solution:
[0046] The holding temperature is 1030-1050°C, and the net holding time is 5-10 min / mm. The steel plate is then taken out of the solution furnace and immediately placed in water for rapid cooling. The cooling rate is not less than 20°C / s. After cooling, the surface temperature of the steel plate is not higher than 50°C.
[0047] Pickling:
[0048] The surface of the solution treated steel plate is cleaned with HF+HNO3 mixed acid at a temperature not higher than 80°C.
[0049] Further; smelting: including EAF electric arc furnace - AOD converter - VOD vacuum refining;
[0050] AOD converter smelting: oxygen and argon are injected into the molten pool. When the carbon content is higher than 0.05%, Ar 2 :O 2 =1:1~1.5 low argon oxygen ratio for blowing, oxygen supply intensity is 3~5m 3 / (t·min), the decarburization rate is 0.2~0.4% / min; when the carbon content is reduced to 0.05%, the argon oxygen ratio is increased to Ar 2 :O 2 =3.5:1~4:1; control the Si content in the steel to below 0.5% and the basicity of the slag to below 2.0;
[0051] VOD vacuum refining: deep decarburization of molten steel.
[0052] First, oxygen blowing decarburization is carried out. The vacuum degree of the VOD vacuum refining furnace is 50-100mbar. When the carbon content in the molten steel drops to 0.03%, the vacuum degree is adjusted to 20-40mbar. When the carbon content reaches 0.01%, oxygen blowing is stopped and the vacuum degree is controlled to drop to 1-10mbar. At the same time, bottom stirring is strengthened to carry out vacuum decarburization.
[0053] The composition of the steel of the embodiment of the present invention is shown in Table 1. The main process parameters for smelting the steel of the embodiment of the present invention are shown in Table 2. The main process parameters for rolling the steel of the embodiment of the present invention are shown in Table 3. The main process parameters for solution treatment of the steel of the embodiment of the present invention and the microstructure of the steel plate are shown in Table 4. The properties of the steel of the embodiment of the present invention are shown in Table 5. The low temperature fracture properties of the steel of the embodiment of the present invention are shown in Table 6. The corrosion resistance of the steel of the present invention is shown in Table 7.
[0054] Table 1 Composition of steel according to the present invention (wt%)
[0055]
[0056] Table 2 Main process parameters for steel smelting in the embodiment of the present invention
[0057]
[0058] Table 3 Main process parameters of steel rolling in the embodiment of the present invention
[0059]
[0060] Table 4 Main process parameters of solution treatment of steel and microstructure of steel plate in the embodiment of the present invention
[0061]
[0062] Table 5 Properties of steel according to the present invention
[0063]
[0064] Table 6 Low temperature fracture performance of steel according to the present invention
[0065]
[0066] Table 7 Corrosion resistance of the steel of the present invention
[0067]
[0068] The present invention is used to produce polar ship duplex stainless steel plates, the microstructure of which is austenite and ferrite, wherein the volume percentage is: austenite phase: 60% to 80%, ferrite: 20% to 40%; the average grain size of the duplex stainless steel plate can be controlled at 10 to 20 μm. The plate has high strength (yield strength ≥ 605MPa, tensile strength ≥ 812MPa), low temperature resistance (-80℃ impact energy ≥ 180J, -100℃ impact energy ≥ 142J, no plastic transition temperature NDTT ≤ -70℃), (-40℃) low temperature elongation ≥ 35%, Z-direction performance ≥ 63%, low temperature fracture (-20℃, -40℃, -60℃) CTOD characteristic value of parent material and heat affected zone> 0.2mm, and the pitting corrosion performance is measured according to ASTM G48 method A ferric chloride test method. The pitting corrosion rate of the steel plate is 0.0030 to 0.0065g / m 2 h; The intergranular corrosion performance was measured according to ASTM A262 method E and the steel plates showed no cracks; its good conventional mechanical properties, corrosion resistance, low-temperature fracture toughness, etc. can meet the technical requirements of marine steel plates for harsh and demanding service conditions in the polar marine environment.
[0069] In order to describe the present invention, the present invention is appropriately and fully illustrated by the examples in the above. The above implementation modes are only used to illustrate the present invention, but not to limit the present invention. Ordinary technicians in the relevant technical field can make various changes and modifications without departing from the spirit and scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made should be included in the protection scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A polar marine duplex stainless steel plate with excellent low temperature fracture toughness, characterized in that: The composition of the steel plate is as follows by weight percentage: C: 0.001% to 0.01%, Si: 0.2% to 0.5%, Mn: 0.5% to 1.5%, P≤0.02%, S≤0.002%, Cr: 21% to 22%, Ni: 7% to 9%, Mo: 2% to 3%, N: 0.1% to 0.3%, Cu: 2% to 3%, La: 0.0055% to 0.0095%, Ce: 0.0045% to 0.0085%, and the balance is iron and unavoidable impurities.
2. A polar marine duplex stainless steel plate with excellent low temperature fracture toughness, characterized in that: The microstructure of the duplex stainless steel plate is austenite and ferrite, wherein the volume percentage is: austenite phase: 60% to 80%, ferrite: 20% to 40%; the average grain size of the duplex stainless steel plate can be controlled at 10 to 20 μm.
3. A polar marine duplex stainless steel plate with excellent low temperature fracture toughness, characterized in that: The stainless steel plate has a yield strength of ≥605MPa, a tensile strength of ≥812MPa, an impact energy of ≥180J at -80°C, an impact energy of ≥142J at -100°C, a non-plastic transition temperature NDTT≤-70°C, a low-temperature elongation of ≥35% at -40°C, Z-direction performance ≥63%, and a low-temperature fracture CTOD of the base material and the heat-affected zone of >0.2mm at -20°C, -40°C and -60°C.
4. A method for manufacturing a polar shipbuilding duplex stainless steel plate with excellent low-temperature fracture toughness as claimed in claims 1 to 3, comprising smelting, rolling and solid solution; characterized in that: Rolling: the ingot is loaded into a heating furnace at a furnace temperature of 800-850°C and kept warm for 1.5-2 hours; the ambulation temperature is 1200-1250°C and kept warm for 2-2.5 hours; two-stage rolling is adopted, the first stage rolling is carried out in a low temperature and large reduction manner, the start rolling temperature is controlled at 1100-1150°C, the pass reduction rate is 20%-25%, and the first stage final rolling temperature is 1050-1100°C; the second stage is carried out in a small reduction manner, the start rolling temperature is 1000-1050°C, the pass reduction rate is 10%-15%, and the final rolling temperature is above 950°C. The steel plate is air-cooled to room temperature after rolling; Solid solution: The insulation temperature is 1030-1050°C, and the net insulation time is 5-10 min / mm. The steel plate is then immediately placed in water for rapid cooling, with a cooling rate of not less than 20°C / s. After cooling, the surface temperature of the steel plate is not higher than 50°C.
5. The method for manufacturing a polar shipbuilding duplex stainless steel plate with excellent low-temperature fracture toughness according to claim 4, characterized in that: Smelting: including EAF electric arc furnace - AOD converter smelting - VOD vacuum refining; AOD converter smelting: oxygen and argon are blown into the molten pool. When the carbon content is higher than 0.05%, a low argon-oxygen ratio of Ar2:O2=1:(1-1.5) is used for blowing, and the oxygen supply intensity is 3-5m 3 / (t·min), the decarburization rate is 0.2~0.4% / min; when the carbon content is reduced to 0.05%, the argon oxygen ratio is increased to Ar2:O2=(3.5~4):1; the Si content in the steel is controlled below 0.5%, and the basicity of the slag is controlled below 2.0; VOD vacuum refining: deep decarburization of molten steel. First, oxygen blowing decarburization is carried out, and the vacuum degree of the VOD vacuum refining furnace is 50-100mbar; when the carbon content in the molten steel drops to 0.03%, the vacuum degree is adjusted to 20-40mbar; when the carbon content reaches 0.01%, oxygen blowing is stopped, and the vacuum degree is controlled to drop to 1-10mbar; at the same time, bottom stirring is strengthened to carry out vacuum decarburization.
Citation Information
Patent Citations
Corrosion-resistant high-strength duplex stainless steel and preparation method thereof
CN116904854A
Preparation method of high-performance duplex stainless steel
CN117535478A
Cited By
Thick low-temperature-resistant high-toughness duplex stainless steel
CN120818754A